Comprehensive formation of leather semi-finished products using enzymes - Danylkovych, Аnatolii; Okhmat, Olena (Technology audit and production reserves, 2025)
The object of research is the process of complex formation of elastic leather using enzymes of proteolytic and hydrolytic action. One of the most problematic areas is the decrease in the elasticity of the leather semi-finished product at the stage of its dehydration. Enzyme treatment increases the mobility of the microfibrillar structure of the semi-finished product due to the destruction of physical intermolecular bonds. During the study, a proteolytic enzyme was used at the stage of bating the pelt and enzymes of hydrolytic action were used to treat the tanned chrome semi-finished product. A semi-finished product was obtained, which is characterized by an increase in porosity compared to the original semi-finished product. The porosity of the semi-finished product increases by 22% in the case of using enzyme treatment at the bating stage and by 67% with repeated treatment of the tanned semi-finished product with enzymes. This is due to the fact that the proposed enzyme treatment promotes the removal of glycosaminoglycans from the dermis at the bating stage. Further use of enzymes after tanning of the semi-finished product contributes to the destruction of carbohydrate bonds with collagen macromolecules, which ensures an increase in its physicochemical properties. The peculiarity of this effect can be explained by the presence of an active center in enzymes, which forms enzyme-hydrocarbon-collagen complexes with carbohydrates and collagen macromolecules. Inside the formed complexes, the destruction of existing bonds occurs and the separation of carbohydrates from the collagen of the dermis. This provides the possibility of obtaining a leather semi-finished product, which is characterized by an increase in the tensile strength and elongation at 9.8 MPa by 8.4 and 23.0%, respectively, and these indicators reach 20.7 MPa and 48.0% compared to the indicators of the tanned semi-finished product.